Tanggung Jawab Hukum Perdata Rumah Sakit dalam Pelayanan Kesehatan terhadap Pasien - Anindya Putri Permatsari; Suriyani Mansyur; Amelia Agustina; Yuyut Prayuti (Institut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to analyze the civil legal liability of hospitals in delivering healthcare services to patients, especially in cases of negligence or violations of medical service standards. A normative juridical approach is employed, utilizing statutory regulations, legal doctrines, and court decisions as primary data sources. The results show that hospitals may be held civilly liable on the grounds of breach of contract or tort, either directly or vicariously for the actions of medical personnel. Provisions in the Indonesian Civil Code, Law No. 36 of 2009 on Health, and Law No. 44 of 2009 on Hospitals serve as the main legal basis in assessing hospital obligations. Legal protection for patients must be strengthened through regulatory oversight and increased legal awareness within healthcare institutions.